The historical development of adult guardianship concerning persons fully or partially deprived of contractual capacity, with specific reference to Bosnia and Herzegovina - Miković Borjana (Zbornik Radova Pravnog Fakulteta u Nišu, 2020)
The institute of adult guardianship has had a long historical development, primarily focused on the care needed for the wards. Yet, the purpose of its application has always depended on the historical circumstances and the time when the particular legislation was adopted. In this respect, in modern law, this institute is linked to a particular person who is incapable of taking care of himself/herself or managing his/her affairs, rights and obligations. The development of this institute in legal history may be traced back to Roman law, which provides the first data on guardianship. These legal solutions were largely accepted in the Austrian Civil Code of 1811, which was the applicable law in Croatia, Slovenia, Dalmatia and partially Istria, in the period of the Austro-Hungarian Empire and at the time of the Kingdom of Serbs, Croats and Slovenians (along with the application of Sharia Law for Muslims). Serbia adopted a separate Law on Guardianship in 1872. After the end of World War II, the first Basic Law on Guardianship in the newly established Yugoslavia was adopted in 1947, which was replaced by a new Guardianship Act of 1965. This particular Act was in force in B&H until the adoption of the Family Act of the Socialist Republic of B&H (1979). Currently, the application of the institute of adult guardianship in B&H has been regulated by three separate Family Acts, which will be discussed in this paper